Cultural intelligence and employees' creative performance: The moderating role of team conflict in interorganizational teams. (17th January 2017) - Hu, Nan; Wu, Jianlin; Gu, Jibao
Abstract: Recently, an increasing number of organizations conduct collaborative innovation by establishing interorganizational teams comprising employees from different organizations. Given that employees face immense challenges because of organizational culture differences in interorganizational teams, this study focused considerably on cultural intelligence in the interorganizational context. This cultural intelligence refers to the ability of individuals to deal effectively with organizational culture differences. Our research particularly explored the effect of employees' cultural intelligence on their creative performance and the moderating effects of two types of team conflicts through hierarchical linear modeling. The sample was obtained from 54 interorganizational teams that included 275 employees. Results confirmed a positive relationship between employees' cultural intelligence and their creative performance and the positive relationship will be stronger in higher relationship conflicts and lower task conflicts. The theoretical and practical implications of this study were also discussed.